Aging abolishes circadian rhythms of RORα and antioxidant enzymes expression in temporal cortex of free running rats - Deyurka, Nicolás Andrés (2018)
RORα is a transcription factor that binds RORE motifs in the promoter of clock Bmal1 and othertarget genes. Antioxidant enzymes contribute to the cellular redox state which is crucial for themolecular clock function. Previously, we showed antioxidant enzymes activity follow a dailyvariation in temporal cortex (TC), which was abolished in aged rats. Herein we aimed: 1) toinvestigate endogenous rhythms of Cat, Gpx and Nrf2 genes expression and RORα protein levels inrat TC, and 2) to evaluate whether aging could affect those temporal patterns. Three- and 22-monthold male Holtzman rats were maintained under constant darkness for 15 days before the experiment,in order to validate the endogenous nature of circadian rhythms. TC samples were isolated every 4h during a 24h period. RORα protein levels were assessed by immunoblotting. Cat, Gpx and Nrf2 mRNA levels were determined by RT-PCR. Specific softwares were used to circadian analysis. We observed circadian endogenous rhythms of RORα, Cat and Gpx expression in the TC of young freerunning rats (Chronos fit, p<0.05, p< 0.001 and p<0.05, respectively). We found Ebox and RORE sites in the Cat and Gpx genes regulatory regions. RORα rhythm?s acrophase occurs at the beginning of the subjective day, preceding Cat and Gpx mRNA peaks. Consistent with previous results, aging abolishes RORα, Cat, and Gpx circadian rhythms in TC. Interestingly, Nrf2 gene expression becomes rhythmic in the TC of aged rats. Our observations would contribute to the knowledge of circadian alterations in TC of the aged brain.